Public diplomacy of the Republic of Finland and features of its implementation in Ukraine - Olha Anisimovych-Shevchuk; Valeriia Troian (Language, Culture, Politics)
The article is focused on public diplomacy viewed as the instrument of “soft power” of the state and the ability to persuade and create reputation as well as cultural and institutional attractiveness. Moreover, the paper emphasizes the importance of the correct formation of priorities and values of the state, and skillful national branding. The authors pay a particular attention to the foreign policy of the Republic of Finland in the context of public diplomacy service. Hence, developmental phases of the Finnish public diplomacy were given. In addition, a special attention was paid to the functional features of public authorities with reference to public diplomacy viewed as an important factor in international relations and the national interest protection of Finland. Therefore, the spheres of public diplomacy such as the cultural, educational-scientific, public, or digital diplomacy of Finland are under analysis, too. Additionally, the means and methods of public diplomacy, including those practiced in Ukraine were under particular attention. Thus, a special emphasis was put on the national brandmark and international position of the State. Based on the conducted empirical research which confirms the necessity of further cooperation between Ukraine and Finland, aimed at implementation of public diplomacy tools, there were given recommendations concerning the execution of the means and methods of “soft power”.